2018
DOI: 10.1124/dmd.118.084293
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Models of Drug Metabolism, Transporters, and Toxicity

Abstract: This commentary summarizes expert mini-reviews and original research articles that have been assembled in a special issue on novel models of drug metabolism and disposition. The special issue consists of research articles or reviews on novel static or microflow based models of the intestine, liver, eye, and kidney. This issue reviews static intestinal systems like mucosal scrapings and cryopreserved intestinal enterocytes, as well as novel bioengineered or chemically engineered intestinal models derived from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Drugs undergo biotransformations, and thus the optimization of the drug structure per se could be useless when significant metabolic liability, generating novel compounds (metabolites), occurs. In the last two decades, many efforts have been made to decode and predict the metabolic fate of drugs, and in silico models, in vitro assays, and hybrid approaches (i.e., innovative assays associated with software-assisted data processing) , have been developed to identify the “soft spots” of drugs. Despite signs of progress in the field, all available ADME tools have been calibrated mainly using the chemical space of small molecules, witnessing the outstanding impact that the Lipinski rules have had in pharmaceutical research in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs undergo biotransformations, and thus the optimization of the drug structure per se could be useless when significant metabolic liability, generating novel compounds (metabolites), occurs. In the last two decades, many efforts have been made to decode and predict the metabolic fate of drugs, and in silico models, in vitro assays, and hybrid approaches (i.e., innovative assays associated with software-assisted data processing) , have been developed to identify the “soft spots” of drugs. Despite signs of progress in the field, all available ADME tools have been calibrated mainly using the chemical space of small molecules, witnessing the outstanding impact that the Lipinski rules have had in pharmaceutical research in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Whole cells such as primary hepatocytes, cultured hepatic mono/cocultures (e.g., with Kupffer cells) and derived cell lines (e.g., HepG2) are also used in DDI studies for estimation of multiple uptakes, metabolism, and/or efflux kinetic parameters (Zamek‐Gliszczynski et al., 2013). Novel hepatic systems such as cryopermeabilized Metmax hepatocytes and longer term hepatocyte coculture systems, micropattern hepatocyte cocultures, 3D liver spheroids, and microfluidic systems are available on the market for use in the drug disposition studies (Sawant‐Basak & Obach, 2018). As reviewed and discussed by Bale and Borenstein (2018), unlike conventional cryopreserved hepatocyte suspension assays, hepatic microfluidic coculture systems (hepatocytes with Kupffer and/or stellate cells) capture dynamic, human‐relevant behavior, and allow to study complex underlying mechanisms of nutrient transport, drug‐disease interactions, and the metabolism‐transport interplay.…”
Section: Evaluation Of Tddismentioning
confidence: 99%
“…However, it has been shown that the microenvironment of the in vivo tumor is different from the 2D monolayer cell cultures 2 . It has been also described that three-dimensional (3D) cell cultures are physiologically more relevant model systems for drug testing 3 and cancer research because they enable the examination of drug penetration and tumor development 4 , 5 . One of the most common 3D cell cultures is the spheroid models where the cells aggregate, produce an extracellular matrix, consequently form a sphere-like structure 6 .…”
Section: Introductionmentioning
confidence: 99%